Chronic Stress Exposure Suppresses Mammary Tumor Growth and Reduces Circulating Exosome TGF-β Content via β-Adrenergic Receptor Signaling in MMTV-PyMT Mice. - Dawes, Ryan P; Burke, Kathleen A; Byun, Daniel K; Xu, Zhou; Stastka, Petr; Chan, Leland; Brown, Edward B; Madden, Kelley S (Breast Cancer: Basic & Clinical Research, 2020)
Preclinical models of breast cancer have established mechanistic links between psychological stress and cancer progression. However, epidemiological evidence linking stress and cancer is equivocal. We tested the impact of stress exposure in female mice expressing the mouse mammary tumor virus polyoma middle-T antigen (MMTV-PyMT), a spontaneous model of mammary adenocarcinoma that mimics metastatic hormone receptor–positive human breast cancer development. MMTV-PyMT mice were socially isolated at 6 to 7 weeks of age during premalignant hyperplasia. To increase the potency of the stressor, singly housed mice were exposed to acute restraint stress (2 hours per day for 3 consecutive days) at 8 to 9 weeks of age during early carcinoma. Exposure to this dual stressor activated both major stress pathways, the sympathetic nervous system and hypothalamic-pituitary-adrenal axis throughout malignant transformation. Stressor exposure reduced mammary tumor burden in association with increased tumor cleaved caspase-3 expression, indicative of increased cell apoptosis. Stress exposure transiently increased tumor vascular endothelial growth factor and reduced tumor interleukin-6, but no other significant alterations in immune/inflammation-associated chemokines and cytokines or changes in myeloid cell populations were detected in tumors. No stress-induced change in second-harmonic generation-emitting collagen, indicative of a switch to a metastasis-promoting tumor extracellular matrix, was detected. Systemic indicators of slowed tumor progression included reduced myeloid-derived suppressor cell (MDSC) frequency in lung and spleen, and decreased transforming growth factor β (TGF-β) content in circulating exosomes, nanometer-sized particles associated with tumor progression. Chronic β-adrenergic receptor (β-AR) blockade with nadolol abrogated stress-induced alterations in tumor burden and cleaved caspase-3 expression, lung MDSC frequency, and exosomal TGF-β content. Despite the evidence for reduced tumor growth, metastatic lesions in the lung were not altered by stress exposure. Unexpectedly, β-blockade in nonstressed mice increased lung metastatic lesions and splenic MDSC frequency, suggesting that in MMTV-PyMT mice, β-AR activation also inhibits tumor progression in the absence of stress exposure. Together, these results suggest stress exposure can act through β-AR signaling to slow primary tumor growth in MMTV-PyMT mice.